Kendala Penyelesaian Tugas Akhir - Enjela Dwi Ananda; Wawan Purwanto (Universitas Negeri Padang, 2021)
This research aims to investigate the inhibit final project of students’ D3 Program in the Automotive Engineering Department Faculty of Engineering Padang State University in 2016 and 2017. The type of this research is descriptive correlational with a population 0f 74 students and 44 students for sample . Based on results that have beeen analyzes, it can be concluded that Instrumental Factors are the most influencing factors on the inhibiting final project of students’ D3 Program in the Automotive Engineering Department Faculty of Engineering Padang State University in 2016 and 2017 because of their TCR value 56,06%, its categorized into four indicators; ability to write scientific papers in the very poor category (54,60%); The effect of availability of learning resources in the less category (57,84%); The family economic conditions in the less category (60,32%); Quality of undergraduate final Project in the very poor category (40,53%). Tujuan penelitian ini untuk mengetahui kendala penyelesaian tugas akhir mahasiswa D3 Teknik Otomotif Fakultas Teknik Universitas Negeri Padang tahun masuk 2016 dan 2017. Jenis Penelitian ini adalah deskriptif korelasional dengan populasi sebanyak 74 mahasiswa dan diambil 44 mahasiswa sebagai sampel. Dari hasil analisis diketahui bahwa Faktor Instrumental menjadi variabel yang paling mempengaruhi kendala penyelesaian tugas akhir mahasiswa D3 Teknik Otomotif Fakultas Teknik Universitas Negeri Padang tahun masuk 2016 dan 2017 karena memiliki nilai TCR sebesar 56,06%, dijabarkan dalam 4 indikator yaitu Kemampuan Menulis Karya Ilmiah pada kategori sangat kurang (54,60%); Ketersediaan Sumber Belajar pada kategori kurang (57,84%); Keadaan Ekonomi Keluarga pada kategori kurang (60,32%); Kualitas Bimbingan pada kategori sangat kurang (40,53%).